Barriers of Implementing Balanced Scorecard in Jordan: a Case Study of Jordanian Banks - Abd Al-Rahman Jaradat; Syamsul Azri bin Abdul Rahman (Economia: Journal of Economics and Management, 2022)
This study aimed to find the existing barriers facing Balanced Scorecard implementation as a performance measurement and management tool in the Jordanian banks. Qualitative research semi-structured interviews were conducted with nine Jordanian commercial bank managers using open-ended questions. The data was analyzed using cross-case analysis. The study showed that lack of top management support, absence of employee participation, inefficient communication between employees and between management levels, lack of knowledge, lack of information technology support, limited education and training, employee resistance, and insufficient funds were the existing challenges in Jordanian bank which would affect the strategy implementation.